Un palais pour les immigrés ? - Andréa Delaplace (Les Cahiers de l'École du Louvre)
With globalization and the emergence of new immigration policies in the European Community, the question of migrations is present at the heart of the politics today. And it is in this historical context of countries of immigration or emigration that the study of museums of immigration, which belong to the category of museums of history and society, are being undertaken or planned. In France, the Cité nationale de l’histoire de l’immigration, which opened its doors in October 2007, has distinguished itself in this global context through its originality and the debate it has created in various domains (from academia to the networks of immigrant associations in France). The museum presents a historical and cultural approach to immigration as well as works of contemporary art relating to the subject. The present article will examine how the museum constitutes an attempt to recognise the heritage of immigration as a national heritage.